2017
DOI: 10.1103/physrevd.96.016015
|View full text |Cite
|
Sign up to set email alerts
|

Cut moments approach in the analysis of DIS data

Abstract: We review the main results on the generalization of the DGLAP evolution equations within the cut Mellin moments (CMM) approach, which allows one to overcome the problem of kinematic constraints in Bjorken x. CMM obtained by multiple integrations as well as multiple differentiations of the original parton distribution also satisfy the DGLAP equations with the simply transformed evolution kernel. The CMM approach provides novel tools to test QCD; here we present one of them. Using appropriate classes of CMM, we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(24 citation statements)
references
References 24 publications
1
23
0
Order By: Relevance
“…In the meantime, only the twist-four term among all the HT corrections needs to be included for our precision goal. There are several recent determinations of the coefficient µ p−n 4 [108][109][110] that are largely consistent with each other. In this work we quote the value µ p−n 4 = (−0.047 ± 0.020)M 2 in ref.…”
Section: Jhep10(2021)053supporting
confidence: 62%
See 1 more Smart Citation
“…In the meantime, only the twist-four term among all the HT corrections needs to be included for our precision goal. There are several recent determinations of the coefficient µ p−n 4 [108][109][110] that are largely consistent with each other. In this work we quote the value µ p−n 4 = (−0.047 ± 0.020)M 2 in ref.…”
Section: Jhep10(2021)053supporting
confidence: 62%
“…In this work we quote the value µ p−n 4 = (−0.047 ± 0.020)M 2 in ref. [109]. We find that at 2 GeV 2 , the inclusion of the twist-four correction reduces the size of Γ p−n 1,th by about 13%, but its total contribution to d 1 through the integral at Q 2 > 2 GeV 2 is only about 1%.…”
Section: Jhep10(2021)053mentioning
confidence: 72%
“…In this subsection, we compare the results for the BSR obtained here for the optimized PT series for the leading twist contributions with the experimental measurements of COMPASS [18][19][20] (taking into account the results of truncated moments [11,12,21]), the E155 Collaboration at SLAC [22], and JLab EG1-DVCS [23]. These optimized estimates are expectedly higher than the conventional ones.…”
Section: B Optimized Bjorken Sum Rule Vs Different Experimental Resultsmentioning
confidence: 98%
“…Including in the estimates of Eq. (1) also the HT contributions with the values µ p−n 4(kmtk) /M 2 [11] and µ p−n 4(JLab) /M 2 [23], we obtain…”
Section: Optimized Bjorken Sum Rule For Slac E155 Collaboration Measumentioning
confidence: 99%
“…The ratio parameter r ≡ z 1 /z 2 and x 0 < x min < r < 1. We have tested all methods of estimation of Γ 1 (0) described in [10] and found that a very effective method, universal for the different small-x behavior of g 1 and for x min 0.1, is the first order approximation, Eq. (11).…”
Section: Two-point Estimation Of γ 1 (0)mentioning
confidence: 99%